Class inequalities in educational attainment among the adult population in the Republic of Ireland - Whelan, Christopher T.; Hannan, Damian F. (Economic & Social Studies, 1999)
Substantial increases in participation rates at secondary and third level in recent years have often been assumed to be associated with increased equality of opportunity. However, there is little evidence from elsewhere that expansion per se, except when it takes the form of saturation of the demand from higher classes, leads to a reduction in class inequalities. In exploring the factors that contribute to trends over time, or to a distinctive position in comparison with other countries, we have drawn on the recent literature to argue that the crucial factors are those which affect decisions to continue in education. We have also operated on the assumption that students and their parents rationally consider the costs and benefits associated with educational choices. The most recent evidence relating to the adult population provides no support for the existence of any trend towards equality of educational opportunity. It is, rather consistent with the class reproduction perspective that stresses the ability of privileged classes to maintain their advantages.
Keywords: Inequality; Educational attainment; Adult educational opportunities; Ireland; Social class